The evaluation performance of letter-based technique on text steganography system - Roshidi Din; Rosmadi Bakar; Sunariya Utama; Jamaluddin Jasmis; Shamsul Jamel Elias (Bulletin of Electrical Engineering and Informatics, 2019)
Steganography is a part of information hiding in covering the hidden message in any medium such as text, image, audio, video and others. This paper concerns about the implementation of steganography in text domain called text steganography. It intends to concentrate on letter-based technique as one of the representative techniques in text steganography. This paper displays some techniques of letter-based that is integrated in one system technique displayeed in a logical and physical design. The integrated system is evaluated using some parameter that is used in order to discover the performance in term of capacity after embedding process and the time consuming in the development process. This paper is anticipated to contribute in describing the implementation of the techniques in one system and to display the performance some parameter evaluation.